Method for preparing mesophase pitch from aromatic hydrocarbon-rich heavy oil

By adding heteropolyate salt and magnetic organic iron macromolecular complex to the catalytic cracked oil slurry to conduct heat condensation reaction, combined with nitrogen stripping method and microwave heating and precipitation process, the problems of complex and low yield of mesophase asphalt preparation process in the prior art are solved, and the preparation of mesophase asphalt with high purity and low softening points is achieved, which has the advantages of simplifying the process, improving yield and reducing costs.

CN119776024APending Publication Date: 2025-04-08PETROCHINA KARAMAY PETROCHEMICAL CO LTD +1

Patent Information

Application Number
CN202311293279.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has problems such as complex process routes, difficulty in achieving continuous operation, low yields of mesophase asphalt, difficult to recover extractant, easy secondary pollution, and residual heteroatoms in the product.

Method used

Catalytic cracked oil slurry (FCC) is used as raw material, and heteropolyte salt is added as an initiator and magnetic organic iron macromolecular complex for heat condensation reaction. Combined with nitrogen stripping method and microwave heating precipitation process, separate and settle under weak magnetic fields and strong magnetic fields, light components and impurities are removed, and the mesophase asphalt with high purity and low softening points is produced.

Benefits of technology

The high purity and low softening points of mesophase asphalt are achieved, the process route is simplified, the yield and quality of mesophase asphalt is improved, the production cost is reduced, and it has the advantages of large operable space and high universality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of mesophase pitch preparation, in particular to a method for preparing mesophase pitch from aromatic hydrocarbon-rich heavy oil, which comprises the following steps: by taking catalytic cracking slurry oil as a raw material, adding a proper amount of initiator and magnetic organic iron macromolecular complex, and preparing two-phase coexisting pitch through thermal polycondensation reaction under certain conditions; then, removing light components in the asphalt by adopting a nitrogen stripping method, separating and settling the asphalt containing the intermediate phase components by utilizing a low-intensity magnetic field assisted microwave heating settling process, and finally, taking heavy components in the intermediate phase components at the lower layer, inducing iron-containing impurities to settle and remove under the action of a high-intensity magnetic field. Therefore, the mesophase pitch with high purity and low softening point is obtained. The invention provides a brand new treatment process with high treatment efficiency, can realize high value-added utilization of various aromatic hydrocarbon-rich heavy oil, and has the advantages of large operable space and high universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mesophase asphalt preparation, in particular to a method for preparing mesophase asphalt from aromatics-rich heavy oil. Background Art

[0002] Mesophase asphalt is a special liquid crystal material formed by the oriented stacking of polycyclic aromatic hydrocarbon molecules with high molecular weight under the influence of intermolecular forces. It has optical anisotropy, good fluidity in the molten state, and is easy to be processed to prepare a variety of carbon materials with excellent performance, such as carbon fiber, needle coke, foamed carbon, etc. Mesophase asphalt is usually made of coal tar or petroleum-based heavy oil. Under certain reaction conditions, it undergoes dehydrogenation, polycondensation, aromatization and other reaction processes to form aromatic hydrocarbon aggregates with optical anisotropy. Common processes for preparing mesophase asphalt include: thermal polycondensation, catalytic polycondensation, co-carbonization, potential mesophase method, etc. In actual production, it is usually combined with the composition characteristics of the raw oil and the needs of the application field to select a suitable single or combined process to prepare mesophase asphalt with excellent performance.

[0003] A Chinese patent document with publication number CN110699107A discloses a method for preparing spinnable mesophase asphalt by hydrogen catalysis and hydrogen supply treatment of coal tar pitch. The method uses coal tar pitch as raw material, obtains refined hydrogenated asphalt by two high-temperature hydrogen treatments, and then obtains spinnable mesophase asphalt by thermal polycondensation reaction. The process route of the invention is complicated, it is difficult to achieve continuous operation, and the yield of mesophase asphalt is low.

[0004] A Chinese patent document with publication number CN108795467A discloses a method for preparing mesophase asphalt by extraction separation and thermal polycondensation of FCC clarified oil. This method uses an extractant to extract FCC clarified oil to obtain extractant-insoluble components, which are used as raw materials to carry out thermal polycondensation reaction at a certain temperature and pressure to prepare mesophase asphalt. This method is difficult to recover the extractant and is prone to secondary pollution. At the same time, the solid particles remaining in the insoluble components of the FCC oil slurry obtained by extraction will affect the secondary processing performance of the mesophase asphalt.

[0005] A Chinese patent document with publication number CN102899061A discloses a method for preparing high-purity mesophase asphalt, which uses refined naphthalene as a raw material and anhydrous AlCl3 as a catalyst, performs a catalytic polycondensation reaction under certain reaction conditions, and removes residual AlCl3 from the reaction product by acid and alkali washing. When obtaining the mesophase asphalt, a large amount of acid and alkali waste liquid is inevitably generated, which pollutes the environment and increases production costs, and a small amount of heteroatoms will remain in the product asphalt.

[0006] The direct thermal polycondensation method is the most primitive preparation method for mesophase asphalt, which has the advantages of simple procedures and easy control of process conditions. However, the mesophase asphalt prepared by this method has a low H / C atomic ratio and a high softening point, which is prone to excessive carbonization. Although the catalytic polycondensation method can obtain low softening point and high purity mesophase asphalt, on the one hand, this method has the problem that the catalyst is difficult to completely remove, the steps are complicated, and the cost is high. On the other hand, due to the extremely strong corrosiveness of superacids, strict requirements are placed on the equipment material during the production process, and there are certain safety risks. Summary of the invention

[0007] The present invention provides a method for preparing mesophase asphalt from aromatics-rich heavy oil, which overcomes the shortcomings of the above-mentioned prior art. The mesophase asphalt prepared by the method has the characteristics of high purity and low softening point.

[0008] The technical solution of the present invention is achieved by the following measures: A method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, using catalytic cracking oil (FCC) as a raw material, adding a required amount of initiator and magnetic organic iron macromolecular complex into the catalytic cracking oil (FCC) to carry out thermal polycondensation reaction to obtain asphalt containing light components and intermediate phase components; S2, stripping the asphalt containing light components and mesophase components by nitrogen stripping to remove the light components in the asphalt to obtain the asphalt containing the mesophase components, separating and settling the asphalt containing the mesophase components by microwave heating sedimentation process under a weak magnetic field, discarding the upper layer, and obtaining the heavy component asphalt in the lower mesophase components; S3, separating and settling the heavy component asphalt in the lower intermediate phase component under a strong magnetic field to remove iron-containing impurities and obtain high-purity, low-softening-point intermediate phase asphalt.

[0009] The following are further optimizations and / or improvements to the above technical solutions: The initiator is a heteropolyacid iron salt, and the heteropolyacid iron salt is one or more of ferric pyrosulfate, ferric tungstate phosphate, ferric molybdate phosphate, and ferrosiliconic acid.

[0010] The magnetic organic iron macromolecular complex is one of a cellulose iron sodium complex, an iron hydroxide-sucrose complex, a chlorophyll iron complex, and an iron gluconate sodium complex.

[0011] The added amount of the above initiator is 0.1wt% to 3.0wt% of the weight of the catalytic cracking oil slurry.

[0012] The addition amount of the magnetic organic iron macromolecular complex is 0.2wt% to 0.8twt% of the weight of the catalytic cracking oil slurry.

[0013] In the above step S1, the thermal polycondensation reaction temperature is 350° C. to 400° C., the reaction pressure is 1 MPa to 3 MPa, and the reaction time is 2 h to 8 h.

[0014] In the above step S2, in the nitrogen stripping method, high-purity nitrogen (purity is 99.999%) is used, the nitrogen flow rate is 10 mL / min to 100 mL / min, and the purge time is 1 h to 3 h.

[0015] In the above step S2, the weak magnetic field strength is 1T to 10T, in the microwave heating sedimentation process, the microwave heating power is 500W to 900W, and the heat sedimentation time is 1h to 3h.

[0016] In the above step S3, the intensity of the strong magnetic field is 100T to 1000T, the sedimentation temperature is 300°C to 350°C, and the sedimentation time is 5min to 20min.

[0017] The present invention utilizes heteropolyacid iron salt initiator in combination with magnetic organic iron macromolecular complex to realize efficient conversion and utilization of catalytic cracking oil slurry under mild reaction conditions, and simultaneously realizes efficient removal of impurity components by combining with magnetic field induced sedimentation process under microwave heating conditions, and finally obtains intermediate phase asphalt with excellent performance. The present invention provides a new processing process with high processing efficiency, which can realize high added value utilization of various aromatics-rich heavy oils, has the advantages of large operating space and high universality, and can be widely used in the preparation of carbon materials such as carbon fiber, carbon microspheres, and needle coke. DETAILED DESCRIPTION

[0018] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art.

[0019] The present invention will be further described below in conjunction with embodiments: Example 1: The method for preparing mesophase asphalt from the aromatics-rich heavy oil is carried out as follows: S1, using catalytic cracking oil (FCC) as a raw material, adding a required amount of initiator and magnetic organic iron macromolecular complex into the catalytic cracking oil (FCC) to carry out thermal polycondensation reaction to obtain asphalt containing light components and intermediate phase components; S2, stripping the asphalt containing light components and mesophase components by nitrogen stripping to remove the light components in the asphalt to obtain the asphalt containing the mesophase components, separating and settling the asphalt containing the mesophase components by microwave heating sedimentation process under a weak magnetic field, discarding the upper layer, and obtaining the heavy component asphalt in the lower mesophase components; S3, separating and settling the heavy component asphalt in the lower intermediate phase component under a strong magnetic field to remove iron-containing impurities and obtain high-purity, low-softening-point intermediate phase asphalt.

[0020] Example 2: As an optimization of the above example, the initiator is a heteropolyacid iron salt, and the heteropolyacid iron salt is one or more of ferric pyrosulfate, ferric tungstate phosphate, ferric molybdate phosphate, and ferrosiliconic acid.

[0021] Example 3: As an optimization of the above example, the magnetic organic iron macromolecular complex is one of a sodium iron cellulose complex, an iron hydroxide-sucrose complex, a chlorophyll iron complex, and a sodium iron gluconate complex.

[0022] In the present invention, the preparation of the sodium iron cellulose complex is as follows: 3 g of sodium carboxymethyl cellulose (CMC) is prepared into a CMC sodium salt solution with a mass concentration of 3%, 3 mL of a 0.02 mol / L ferric chloride solution is added, the mixture is heated and stirred at 90° C. for 30 min, and then cooled to room temperature.

[0023] Preparation of ferric hydroxide-sucrose complex: Take 10g of sucrose and add it to Fe(OH)3 mud, adjust the pH to 10, stir for 30min, heat to 100℃, react for 5h, and cool to room temperature.

[0024] Preparation of chlorophyll iron complex: Dissolve 2.0 g of silkworm excrement chlorophyll extract and 2.0 g of ferric chloride hexahydrate in 150 ml of 15% ammonia water, stir at room temperature for 3 h, adjust the pH to 4 to 5 with dilute hydrochloric acid, filter and collect the precipitate, dry it, and obtain the chlorophyll iron complex through silica gel column chromatography.

[0025] Preparation of sodium ferric gluconate complex: Dissolve 5 g of sodium gluconate in 20 ml of distilled water, add 30 ml of 1 mol / L FeCl3 solution dropwise at room temperature with stirring, and adjust the pH to 11. Reflux and stir at 110°C for 2 h, filter and cool to room temperature, wash with anhydrous ethanol and acetone in turn, and vacuum dry to obtain sodium ferric gluconate complex.

[0026] Example 4: As an optimization of the above example, the amount of initiator added is 0.1wt% to 3.0wt% of the weight of the catalytic cracking oil slurry.

[0027] Example 5: As an optimization of the above example, the addition amount of the magnetic organic iron macromolecular complex is 0.2wt% to 0.8twt% of the weight of the catalytic cracking oil slurry.

[0028] Example 6: As an optimization of the above example, in step S1, the thermal polycondensation reaction temperature is 350°C to 400°C, the reaction pressure is 1MPa to 3MPa, and the reaction time is 2h to 8h.

[0029] Example 7: As an optimization of the above example, in step S2, in the nitrogen stripping method, the nitrogen used is high-purity nitrogen (purity is 99.999%), the nitrogen flow rate is 10 mL / min to 100 mL / min, and the purge time is 1 h to 3 h.

[0030] Example 8: As an optimization of the above example, in step S2, the weak magnetic field strength is 1T to 10T, in the microwave heating sedimentation process, the microwave heating power is 500W to 900W, and the heat sedimentation time is 1h to 3h.

[0031] Example 9: As an optimization of the above example, in step S3, the strength of the strong magnetic field is 100T to 1000T, the sedimentation temperature is 300°C to 350°C, and the sedimentation time is 5min to 20min.

[0032] Embodiment 10: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, using catalytic cracking oil (FCC) as raw material, adding the required amount of initiator (ferric pyrosulfate) and magnetic organic iron macromolecular complex (sodium cellulose iron complex) into 200g of catalytic cracking oil (FCC), and performing thermal polycondensation reaction at a temperature of 350°C and a pressure of 1MPa for 2h to obtain asphalt containing light components and intermediate phase components; wherein the amount of initiator added is 0.1wt% of the weight of the catalytic cracking oil; S2, stripping the asphalt containing light components and intermediate phase components by nitrogen stripping method, removing the light components in the asphalt to obtain the asphalt containing the intermediate phase components, separating and settling the asphalt containing the intermediate phase components under a weak magnetic field with an intensity of 1T and a microwave heating power of 500W, discarding the upper layer, and obtaining the heavy component asphalt in the lower intermediate phase components; wherein the addition amount of the magnetic organic iron macromolecular complex is 0.2wt% of the weight of the catalytic cracking oil slurry; wherein, in the nitrogen stripping method, the nitrogen used is high-purity nitrogen (purity is 99.999%), the nitrogen flow rate is 10mL / min, and the purge time is 1h; S3, separate and settle the heavy component asphalt in the lower intermediate phase component under a strong magnetic field with an intensity of 100T and a temperature of 300°C for 5 minutes to remove iron-containing impurities and obtain a high-purity, low-softening-point intermediate phase asphalt.

[0033] Embodiment 11: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, using catalytic cracking oil (FCC) as raw material, adding the required amount of initiator (ferro tungstate phosphate) and magnetic organic iron macromolecular complex (ferric hydroxide-sucrose complex) into 200g of catalytic cracking oil (FCC), and performing thermal polycondensation reaction at a temperature of 400°C and a pressure of 3MPa for 8h to obtain asphalt containing light components and intermediate phase components; wherein the amount of initiator added is 3.0wt% of the weight of the catalytic cracking oil; S2, stripping the asphalt containing light components and intermediate phase components by nitrogen stripping method, removing the light components in the asphalt to obtain the asphalt containing the intermediate phase components, separating and settling the asphalt containing the intermediate phase components under a weak magnetic field with an intensity of 10T and a microwave heating power of 900W, discarding the upper layer, and obtaining the heavy component asphalt in the lower intermediate phase components; wherein the addition amount of the magnetic organic iron macromolecular complex is 0.8twt% of the weight of the catalytic cracking oil slurry; wherein, in the nitrogen stripping method, the nitrogen used is high-purity nitrogen (purity is 99.999%), the nitrogen flow rate is 100mL / min, and the purge time is 3h; S3, separate and settle the heavy component asphalt in the lower intermediate phase component at a strong magnetic field of 1000T and a temperature of 350°C for 20 minutes to remove iron-containing impurities and obtain high-purity, low-softening-point intermediate phase asphalt.

[0034] Embodiment 12: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, using catalytic cracking oil (FCC) as raw material, adding the required amount of initiator (ferromolybdate phosphate) and magnetic organic iron macromolecular complex (chlorophyll iron complex) into 200g of catalytic cracking oil (FCC), and performing thermal polycondensation reaction at a temperature of 370°C and a pressure of 2MPa for 5h to obtain asphalt containing light components and intermediate phase components; wherein the amount of initiator added is 2.0wt% of the weight of the catalytic cracking oil; S2, stripping the asphalt containing light components and intermediate phase components by nitrogen stripping method, removing the light components in the asphalt to obtain the asphalt containing the intermediate phase components, separating and settling the asphalt containing the intermediate phase components under a weak magnetic field with an intensity of 5T and a microwave heating power of 700W, discarding the upper layer, and obtaining the heavy component asphalt in the lower intermediate phase components; wherein the addition amount of the magnetic organic iron macromolecular complex is 0.5twt% of the weight of the catalytic cracking oil slurry; wherein, in the nitrogen stripping method, the nitrogen used is high-purity nitrogen (purity is 99.999%), the nitrogen flow rate is 50mL / min, and the purge time is 2h; S3, separate and settle the heavy component asphalt in the lower intermediate phase component at a strong magnetic field of 500T and a temperature of 320°C for 10 minutes to remove iron-containing impurities and obtain high-purity, low-softening-point intermediate phase asphalt.

[0035] In view of the wide molecular weight distribution and uneven reaction activity of catalytic cracking oil (FCC), the present invention establishes a process route for preparing two-phase coexistence asphalt by thermal polycondensation using heteropolyacid iron salt as an initiator and adding a small amount of magnetic organic iron macromolecular complex, wherein the thermal polycondensation of crude oil molecules initiated by the pyrolysis product of heteropolyacid iron salt is highly efficient, which can effectively reduce the reaction temperature, shorten the reaction time, and improve the crude oil conversion rate. At the same time, the magnetic organic iron macromolecular complex can promote the aggregation of mesophase components in addition to initiating the polycondensation reaction, accelerate the separation of the two phases under the influence of a weak magnetic field, and realize the efficient enrichment of the mesophase asphalt. The present invention uses nitrogen stripping to remove light components while generating a gas disturbance effect, which also accelerates the separation of the two phases. With the aggregation effect of the magnetic organic iron macromolecular complex, the iron-containing impurity components are efficiently and quickly precipitated and removed under the induction of a strong magnetic field, and finally a high-purity, low-softening-point mesophase asphalt is obtained.

[0036] Embodiment 13: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, weighing 200g of catalytic cracking oil slurry, 5.6g of ferric pyrosulfate and 1g of sodium cellulose iron complex, adding them into a high temperature and high pressure reactor, and performing a thermal polycondensation reaction at a temperature of 350°C and a pressure of 2MPa for 8h to obtain an asphalt containing a light component and an intermediate phase component; S2, after the reaction is completed, the temperature of the high-temperature and high-pressure reactor is lowered to 300°C, and high-purity nitrogen is introduced into the high-temperature and high-pressure reactor at a nitrogen flow rate of 10 mL / min. The aeration and purge are continued for 1 hour, so that the asphalt containing light components and intermediate phase components in the high-temperature and high-pressure reactor is stripped, and the light components in the asphalt are removed to obtain the asphalt containing the intermediate phase component. Then, the asphalt containing the intermediate phase component is separated and precipitated for 1 hour and 40 minutes at a magnetic field strength of 10T, a microwave heating power of 500W, and a temperature of 300°C. The high-temperature and high-pressure reactor is quickly cooled, and the heavy component asphalt in the lower intermediate phase component is collected; S3, under a magnetic field strength of 500T and a temperature of 300°C, the high-temperature and high-pressure reactor containing the heavy component asphalt in the lower intermediate phase component is settled for 10 minutes, and the iron-containing impurities are removed to obtain an intermediate phase asphalt with an intermediate phase content greater than 93wt% and a softening point of 285°C.

[0037] Embodiment 14: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, weighing 200g of catalytic cracking oil slurry, 3g of ferrosilicon acid and 1.5g of ferric hydroxide-sucrose complex, adding them into a high temperature and high pressure reactor, and performing a thermal polycondensation reaction at a temperature of 360°C and a pressure of 3MPa for 6h to obtain an asphalt containing a light component and an intermediate phase component; S2, after the reaction is completed, the temperature of the high-temperature and high-pressure reactor is lowered to 300°C, and high-purity nitrogen is introduced into the high-temperature and high-pressure reactor at a nitrogen flow rate of 30 mL / min. The aeration and purge are continued for 1.5 hours, so that the asphalt containing light components and intermediate phase components in the high-temperature and high-pressure reactor is stripped, and the light components in the asphalt are removed to obtain the asphalt containing the intermediate phase component. Then, the asphalt containing the intermediate phase component is separated and precipitated for 1h40min at a magnetic field intensity of 8T, a microwave heating power of 700W, and a temperature of 300°C. The high-temperature and high-pressure reactor is quickly cooled, and the heavy component asphalt in the lower intermediate phase component is collected; S3, under a magnetic field strength of 1000T and a temperature of 330°C, the high-temperature and high-pressure reactor containing the heavy component asphalt in the lower intermediate phase component is settled for 15 minutes, and the iron-containing impurities are removed to obtain an intermediate phase asphalt with an intermediate phase content greater than 95wt% and a softening point of 290°C.

[0038] Embodiment 15: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, weighing 200g of catalytic cracking oil slurry, 6g of ferric tungstate phosphate and 1.2g of sodium ferric gluconate complex, adding them into a high temperature and high pressure reactor, and performing a thermal polycondensation reaction at a temperature of 370°C and a pressure of 1MPa for 4h to obtain an asphalt containing a light component and an intermediate phase component; S2, after the reaction is completed, the temperature of the high-temperature and high-pressure reactor is lowered to 300°C, and high-purity nitrogen is introduced into the high-temperature and high-pressure reactor at a nitrogen flow rate of 50 mL / min. The aeration and purge are continued for 2 hours, so that the asphalt containing light components and intermediate phase components in the high-temperature and high-pressure reactor is stripped, and the light components in the asphalt are removed to obtain the asphalt containing the intermediate phase component. Then, the asphalt containing the intermediate phase component is separated and precipitated for 1.5 hours at a magnetic field intensity of 6T, a microwave heating power of 900W, and a temperature of 300°C. The high-temperature and high-pressure reactor is quickly cooled, and the heavy component asphalt in the lower intermediate phase component is collected; S3, under a magnetic field strength of 800T and a temperature of 350°C, the high-temperature and high-pressure reactor containing the heavy component asphalt in the lower intermediate phase component is settled for 20 minutes, and the iron-containing impurities are removed to obtain an intermediate phase asphalt with an intermediate phase content greater than 98wt% and a softening point of 295°C.

[0039] Embodiment 16: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, weighing 200g of catalytic cracking oil slurry, 4g of molybdenum ferric phosphate and 0.8g of chlorophyll iron complex, adding them into a high temperature and high pressure reactor, and performing a thermal polycondensation reaction at a temperature of 380°C and a pressure of 1.5MPa for 2h to obtain an asphalt containing a light component and an intermediate phase component; S2, after the reaction is completed, the temperature of the high-temperature and high-pressure reactor is lowered to 300°C, and high-purity nitrogen is introduced into the high-temperature and high-pressure reactor at a nitrogen flow rate of 80 mL / min. The aeration and purge are continued for 2.5 hours, so that the asphalt containing light components and intermediate phase components in the high-temperature and high-pressure reactor is stripped, and the light components in the asphalt are removed to obtain the asphalt containing the intermediate phase component. Then, the asphalt containing the intermediate phase component is separated and precipitated for 1.5 hours at a magnetic field intensity of 4T, a microwave heating power of 600W, and a temperature of 300°C. The high-temperature and high-pressure reactor is quickly cooled, and the heavy component asphalt in the lower intermediate phase component is collected; S3, under a magnetic field strength of 600T and a temperature of 320°C, the high-temperature and high-pressure reactor containing the heavy component asphalt in the lower intermediate phase component is settled for 18 minutes, and the iron-containing impurities are removed to obtain an intermediate phase asphalt with an intermediate phase content greater than 96wt% and a softening point of 293°C.

[0040] Embodiment 17: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, weighing 200g of catalytic cracking oil slurry, 2g of ferric pyrosulfate, 2g of ferric tungstate phosphate and 0.6g of sodium ferric gluconate complex, adding them into a high temperature and high pressure reactor, and performing a thermal polycondensation reaction at a temperature of 390°C and a pressure of 2.5MPa for 7h to obtain an asphalt containing a light component and an intermediate phase component; S2, after the reaction is completed, the temperature of the high-temperature and high-pressure reactor is lowered to 300°C, and high-purity nitrogen is introduced into the high-temperature and high-pressure reactor at a nitrogen flow rate of 100 mL / min. The aeration and purge are continued for 3 hours, so that the asphalt containing light components and intermediate phase components in the high-temperature and high-pressure reactor is stripped, and the light components in the asphalt are removed to obtain the asphalt containing the intermediate phase component. Then, the asphalt containing the intermediate phase component is separated and precipitated for 1.5 hours under a magnetic field strength of 2T, a microwave heating power of 800W, and a temperature of 300°C. The high-temperature and high-pressure reactor is quickly cooled, and the heavy component asphalt in the lower intermediate phase component is collected; S3, under a magnetic field strength of 400T and a temperature of 340°C, the high-temperature and high-pressure reactor containing the heavy component asphalt in the lower intermediate phase component is settled for 12 minutes, and the iron-containing impurities are removed to obtain an intermediate phase asphalt with an intermediate phase content greater than 92wt% and a softening point of 296°C.

[0041] Embodiment 18: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, weighing 200g of catalytic cracking oil slurry, 4g of ferrosilicon acid, 0.3g of sodium cellulose iron complex and 0.3g of chlorophyll iron complex, adding them into a high temperature and high pressure reactor, and performing a thermal polycondensation reaction at a temperature of 400°C and a pressure of 2MPa for 5.5h to obtain an asphalt containing a light component and an intermediate phase component; S2, after the reaction is completed, the temperature of the high-temperature and high-pressure reactor is lowered to 300°C, and high-purity nitrogen is introduced into the high-temperature and high-pressure reactor at a nitrogen flow rate of 60 mL / min. The aeration and purge are continued for 1.5 hours, so that the asphalt containing light components and intermediate phase components in the high-temperature and high-pressure reactor is stripped, and the light components in the asphalt are removed to obtain the asphalt containing the intermediate phase component. Then, the asphalt containing the intermediate phase component is separated and precipitated for 2.5 hours under a magnetic field strength of 2T, a microwave heating power of 750W, and a temperature of 300°C. The high-temperature and high-pressure reactor is quickly cooled, and the heavy component asphalt in the lower intermediate phase component is collected; S3, under a magnetic field strength of 200T and a temperature of 310°C, the high-temperature and high-pressure reactor containing the heavy component asphalt in the lower intermediate phase component is settled for 8 minutes, and the iron-containing impurities are removed to obtain an intermediate phase asphalt with an intermediate phase content greater than 90wt% and a softening point of 291°C.

[0042] Embodiment 19: The method for preparing mesophase asphalt from aromatics-rich heavy oil is carried out as follows: S1, weighing 200g of catalytic cracking oil slurry, 3g of molybdenum ferric phosphate, 3g of ferrosiliconic acid, 0.4g of ferric hydroxide-sucrose complex and 0.4g of sodium ferric gluconate complex, adding them into a high temperature and high pressure reactor, and performing a thermal polycondensation reaction at a temperature of 350°C and a pressure of 1.5MPa for 6.5h to obtain an asphalt containing a light component and an intermediate phase component; S2, after the reaction is completed, the temperature of the high-temperature and high-pressure reactor is lowered to 300°C, and high-purity nitrogen is introduced into the high-temperature and high-pressure reactor at a nitrogen flow rate of 40 mL / min. The aeration and purge are continued for 2 hours, so that the asphalt containing light components and intermediate phase components in the high-temperature and high-pressure reactor is stripped, and the light components in the asphalt are removed to obtain the asphalt containing the intermediate phase component. Then, the asphalt containing the intermediate phase component is separated and precipitated for 1.5 hours at a magnetic field strength of 6.5T, a microwave heating power of 650W, and a temperature of 300°C. The high-temperature and high-pressure reactor is quickly cooled, and the heavy component asphalt in the lower intermediate phase component is collected; S3, under a magnetic field strength of 850T and a temperature of 325°C, the high-temperature and high-pressure reactor containing the heavy component asphalt in the lower intermediate phase component is settled for 6 minutes, and the iron-containing impurities are removed to obtain an intermediate phase asphalt with an intermediate phase content greater than 95wt% and a softening point of 294°C.

[0043] The mesophase asphalt obtained by the method of preparing mesophase asphalt from aromatic-rich heavy oil in Examples 13 to 19 of the present invention has the characteristics of high mesophase content and low softening point, wherein the mesophase content is greater than 90%, and the softening point ranges from 285°C to 296°C.

[0044] In summary, the present invention utilizes heteropolyacid iron salt initiator in combination with magnetic organic iron macromolecular complex to realize efficient conversion and utilization of catalytic cracking oil slurry under mild reaction conditions. At the same time, it is combined with a magnetic field induced sedimentation process under microwave heating conditions to realize efficient removal of impurity components, and finally obtains intermediate phase asphalt with excellent performance. The present invention provides a new processing process with high processing efficiency, which can realize high added value utilization of various aromatic-rich heavy oils, has the advantages of large operating space and high universality, and can be widely used in the preparation of carbon materials such as carbon fiber, carbon microspheres, and needle coke.

[0045] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A method for preparing mesophase asphalt from aromatics-rich heavy oil, characterized in that Proceed as follows: S1, using catalytic cracking oil slurry as raw material, adding a required amount of initiator and magnetic organic iron macromolecular complex into the catalytic cracking oil slurry for thermal polycondensation reaction to obtain asphalt containing light components and intermediate phase components; S2, stripping the asphalt containing light components and mesophase components by nitrogen stripping to remove the light components in the asphalt to obtain the asphalt containing the mesophase components, separating and settling the asphalt containing the mesophase components by microwave heating sedimentation process under a weak magnetic field, discarding the upper layer, and obtaining the heavy component asphalt in the lower mesophase components; S3, separating and settling the heavy component asphalt in the lower intermediate phase component under a strong magnetic field to remove iron-containing impurities and obtain high-purity, low-softening-point intermediate phase asphalt.

2. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to claim 1, characterized in that The initiator is a heteropolyacid iron salt, and the heteropolyacid iron salt is one or more of ferric pyrosulfate, ferric tungstate phosphate, ferric molybdate phosphate, and ferrosiliconic acid.

3. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to claim 1 or 2, characterized in that The magnetic organic iron macromolecular complex is one of a cellulose iron sodium complex, an iron hydroxide-sucrose complex, a chlorophyll iron complex and an iron gluconate sodium complex.

4. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to claim 1, 2 or 3, characterized in that The added amount of the initiator is 0.1wt% to 3.0wt% of the weight of the catalytic cracking oil slurry.

5. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to any one of claims 1 to 4, characterized in that The addition amount of the magnetic organic iron macromolecular complex is 0.2wt% to 0.8twt% of the weight of the catalytic cracking oil slurry.

6. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to any one of claims 1 to 5, characterized in that In step S1, the thermal polycondensation reaction temperature is 350° C. to 400° C., the reaction pressure is 1 MPa to 3 MPa, and the reaction time is 2 h to 8 h.

7. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to any one of claims 1 to 6, characterized in that In step S2, in the nitrogen stripping method, nitrogen with a purity of 99.999% is used, the nitrogen flow rate is 10 mL / min to 100 mL / min, and the purge time is 1 h to 3 h.

8. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to any one of claims 1 to 7, characterized in that In step S2, the weak magnetic field strength is 1T to 10T, in the microwave heating sedimentation process, the microwave heating power is 500W to 900W, and the heat sedimentation time is 1h to 3h.

9. The method for preparing mesophase asphalt from aromatics-rich heavy oil according to any one of claims 1 to 8, characterized in that In step S3, the intensity of the strong magnetic field is 100T to 1000T, the sedimentation temperature is 300°C to 350°C, and the sedimentation time is 5min to 20min.

Citation Information

Patent Citations

  • Method for preparing high-purity mesophase pitch and prepared high-purity mesophase pitch

    CN102899061A

  • Method for preparing mesophase pitch through extraction separation and thermal poly-condensation of FCC (Fluid Catalytic Cracking) clarified oil

    CN108795467A

  • Method for preparing spinnable mesophase pitch through coal pitch hydrocatalysis-hydrogen supply treatment

    CN110699107A

Cited By

  • Coal liquefaction pitch deferrization system and method based on high-gradient magnetic separation

    CN122128005A